PENGARUH LATIHAN H-MOVEMENT DAN X- PATTERN MULTI SKILL TERHADAP KELINCAHAN DALAM PERMAINAN SEPAK BOLA DI SMA NEGERI 10 GOWA - Suwardi, Suwardi; Badaru, Benny; Ihsan, Andi; Sulfitriyono, Sulfitriyono (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2022)
This study aims to determine whether there is an effect of H-Movement and X-Pattern Multi Skill training on agility in the soccer game of students at SMA Negeri 10 Gowa. A total of 20 students became research subjects taken randomly from a total population of 45 students. This study uses an experimental model with "one group pre test-post test design". The instrument used in this study is the shuttle run test to measure agility. Data analysis used a statistical approach through SPSS series 21. The results obtained from the H-Movement exercise with tcount > ttable (13.661> 1.833), so it was concluded that the H-Movement exercise had an effect on agility in soccer games in students at SMA Negeri 10 Gowa. As for the X-Pattern exercise, it was found that tcount > ttable (9,646 > 1,833). so it can be concluded that the X-Pattern exercise affects agility in soccer games for students at SMA Negeri 10 Gowa..